Unmet need for contraception among married women of reproductive age in the slums of Burdwan municipality, West Bengal - Mallick, Anupam; De, Arindam; Sannigrahi, Suman; Taraphdar, Pranita; Dandapat, Soumik; Jha, Aprajita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Use of inappropriate family planning (FP) methods is one of the major reasons for population growth in India. If the determinants of FP methods were understood, it would help to improve the acceptance of the FP methods among the users and thus contribute to a stable population. The study was conducted to assess the unmet need for contraception and its determinants among married women of reproductive age (WRA) group in the slums of Burdwan municipality. Methods: A community based descriptive and cross-sectional study conducted among 330 married WRA in the slums of Burdwan municipality, West Bengal, from November, 2022 to January, 2023. Fifteen slums were selected from 144 slums in the municipality, by simple random sampling (SRS) and from each slum, study subjects were selected by SRS, from a list of married WRA. A pre-designed, pre-tested, semi-structured schedule was used for data collection and data analyse using SPSS-23. Results: Around 51% couples used some methods of FP and 49% did not use any methods. Among non-users, the unmet need was 18.2% for spacing and 15.1% for limiting births. Significant association (p<0.05) among the determinants of FP, was observed with educational status of respondents and age at marriage. Conclusions: Age, education, socio-economic status, age at marriage, age at 1st pregnancy, types and adverse effects of contraception are important determinants both FP methods and unmet need. So proper counselling and assessment of WRA is essential.